2014
DOI: 10.4168/aair.2014.6.4.316
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Inflammation in Older Adults With Asthma-COPD Overlap Syndrome

Abstract: PurposeThe role of systemic inflammation on asthma-COPD overlap syndrome is unknown. This study aimed to examine systemic inflammation in asthma-COPD overlap syndrome, and to identify associations between clinical characteristics and inflammatory mediators in asthma-COPD overlap syndrome.MethodsIn 108 adults older than 55 years comprising healthy controls (n=29), asthma (n=16), COPD (n=21) and asthma-COPD overlap syndrome (n=42), serum high sensitivity C-reactive protein and Interleukin 6 (IL-6) were assayed. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
76
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(85 citation statements)
references
References 42 publications
6
76
1
Order By: Relevance
“…Also, IL-6 levels were higher in patients with cardiovascular disease compared with patients without the disease, suggesting that systemic inflammation leads to comorbid disease. Interestingly, in a univariate logistic regression analysis, FEV 1 % predicted, sputum neutrophil counts, CCI and IL-6 predicted the risk of having ACOS (not sputum eosinophils) [Fu et al 2014]. In contrast, in the EPISCAN study several blood biomarkers were evaluated, namely albumin, α1 antitrypsin, fibrinogen, C-reactive protein, tumour necrosis factor (TNF)-α, IL-6, IL-8 and nitrite/nitrate (NOx).…”
Section: Biomarkersmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, IL-6 levels were higher in patients with cardiovascular disease compared with patients without the disease, suggesting that systemic inflammation leads to comorbid disease. Interestingly, in a univariate logistic regression analysis, FEV 1 % predicted, sputum neutrophil counts, CCI and IL-6 predicted the risk of having ACOS (not sputum eosinophils) [Fu et al 2014]. In contrast, in the EPISCAN study several blood biomarkers were evaluated, namely albumin, α1 antitrypsin, fibrinogen, C-reactive protein, tumour necrosis factor (TNF)-α, IL-6, IL-8 and nitrite/nitrate (NOx).…”
Section: Biomarkersmentioning
confidence: 99%
“…Also, these markers of systemic inflammation are associated with age, smoking [Pinto-Plata et al 2006], comorbid disease, such as cardiovascular disease [Danesh et al 2004], obesity and diabetes [Bastard et al 2006]. High levels of IL-6 are inversely related to FEV 1 [Fu et al 2014;Walter et al 2008], a faster decline in FEV 1 [Thorleifsson et al 2009] and with an increased risk of developing COPD [Yanbaeva et al 2009]. …”
Section: Biomarkersmentioning
confidence: 99%
“…Generally, reversibility of airflow limitation is incomplete in COPD, while that in asthma can be complete [18]. Therefore, asthma and COPD may overlap and converge [19,20]. Our study was to explore the application and clinical value of combining IOS and BDT for differential diagnosis between asthma and COPD.…”
Section: Discussionmentioning
confidence: 99%
“…Study revealed that CRP and IL-6 levels in ACOS patients were higher than asthma patients and similar to COPD patients suggesting that ongoing systemic inflammation in ACOS patients is as worse as COPD patients [29].…”
Section: Inflammation and Biomarkersmentioning
confidence: 99%